Reviews on the Forming Process of Heat Treatable Aluminium Alloys - Ng, Chuan Huat; Md Yahaya, Shamy Nazrein; Lai, Chee Fung; Sharrifuddin, Faizal; Grote, Karl Heinrich (International Journal of Integrated Engineering, 2018)
Available forming process applied for heat treatable aluminium alloy were reviewed and presented in this paper. The reviews emphasized on the heat treatment, application and contribution of the forming methods. Forming methods discussed includes traditional, warm forming, hydroforming, superplastic forming, hot forming with in-die quench (HFQ) and hot press forming (HPF). The effects of forming processes towards heat treatable aluminium alloy were presented through the understanding on each process strengthening phenomena and the heat treating phenomena. These were to ensure better understanding on heat treatable aluminium alloy composition changes throughout forming process. Finally, concluding remarks the underline challenges of forming heat-treatable aluminium alloy and subsequently highlights the potential work that can be applied in order to ensure a more efficient and sustainable manufacturing agenda for heat treatable aluminium alloy. Available forming process applied for heat treatable aluminium alloy were reviewed and presented in this paper. The reviews emphasized on the heat treatment, application and contribution of the forming methods. Forming methods discussed includes traditional, warm forming, hydroforming, superplastic forming, hot forming with in-die quench (HFQ) and hot press forming (HPF). The effects of forming processes towards heat treatable aluminium alloy were presented through the understanding on each process strengthening phenomena and the heat treating phenomena. These were to ensure better understanding on heat treatable aluminium alloy composition changes throughout forming process. Finally, concluding remarks the underline challenges of forming heat-treatable aluminium alloy and subsequently highlights the potential work that can be applied in order to ensure a more efficient and sustainable manufacturing agenda for heat treatable aluminium alloy.